The United Nations High Commissioner for Refugees (UNHCR) the politics and practice of refugee protection into the twenty-first century - Loescher, Gil 1945-2020; Betts, Alexander 1980-; Milner, James 1974- (Routledge, 2008)
This volume outlines the 'United Nations High Commissioner for Refugees' (UNHCR) historical evolution and examines the key challenges faced by the organization as it moves into the twenty-first century. The UNHCR exists to protect refugees fleeing persecution. As refugee movements often trigger concerns over international security and state sovereignty, the organization's work is at the heart of world politics. UNHCR will appeal to students, scholars, and readers with an interest in international relations.
Literaturverz. S. [142] - 143. - 2. ed. 2012 u.d.T.: UNHCR
Keywords: Office of the United Nations High Commissioner for Refugees; Vereinte Nationen -- Hoher Kommissar für Flüchtlinge; Refugees / Government policy; Refugees / International cooperation; Politik; Refugees -- Government policy; Refugees -- International cooperation